INTERCULTURAL COMMUNICATIVE COMPETENCE: A STEP BEYOND COMMUNICATIVE COMPETENCE - Coperías Aguilar, María José (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The concept of ‘communicative competence’, first proposed by Hymes, referred basically to abilities speakers have in their first language. This term, however, was appropriated and reworked (Canale & Swain 1980; van Ek 1986) within the field of foreign language teaching and new approaches or dimensions (sociolingustic, socio-cultural, social, etc.) were added to the original idea. Consequently, the prescriptive model based upon native speaker competence started to be put into question and the replacement of the native speaker by the intercultural speaker as a reference point for the foreign language learner was suggested (Byram & Zarate 1994). Stemming from all these considerations, a model was proposed (Byram 1997) for Intercultural Communicative Competence (ICC), involving one step further in communicative competence.